An Open Label Randomized Controlled Trial to Compare Low Level Pressure Support and T-piece as Strategies for Discontinuation of Mechanical Ventilation in a General Surgical Intensive Care Unit - Kaweesak Chittawatanarat (2018)
Objective: The purpose of this study was to compare the efficacy of continuous low pressure support (PSV) and T-piece as strategies for discontinuation of mechanical ventilation and extubation in a surgical ICU.Patients and Methods: This was a prospective open label randomized control study in surgical ICU patients who were intubated, mechanically ventilated, and who met criteria for a spontaneous breathing trial. Eligible, enrolled patients were randomized to receive low-level pressure supportup to 7 cmH2O (PSV) or T-piece as the mode of their spontaneous breathing trial.Results: A total of 520 patients were randomized (260 in PSV group and 260 in T-piece group). There were no differences between the groups in baseline characteristics except duration of MV before trial was longer in PSV group. There were also no differences in hemodynamic and respiratory measures between groups. The PSV had a significant higher number of SBT attempt before success and extubation. After extubation, the re-intubation within 48 hours had a lower trend in PSV group (PSV vs. T-piece: 10% vs. 14.6%; p=0.11). The pneumonia occurrence, hospital mortality, hospital and ICU length of stay were not significant different between groups. In multivariable analysis, PSV was associated with a lower risk of success at the first SBT (adjusted relative risk, RR 0.79 [95% confidence interval, CI, 0.70 - 0.88]; p<0.001], and a lower risk of re-intubation within 48 hours after extubation (adjusted RR 0.62 [95%CI 0.40 - 0.98]; p=0.04). There were no differences between groups in pneumonia after extubation and in hospital mortality rate.Conclusion: Although PSV needs a higher number of SBT trial before success and extubation, the re-intubation within 48 hours is lower than T piece. However, there were no differences between the groups in term of pneumonia after extubation, hospital mortality as well as ICU and hospital length of stay.